(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Which challenges does the retail banking industry face nowadays? Walking on the path of M. Porters theories, the author tries to open a window in the retail bankings present and future, the challenges the industry faces, the main forces that shape the competition, the strategies deployed in order to create a competitive advantage for the industry players, and a short prognosis for the industrys future